2018
DOI: 10.1155/2018/6743520
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Associated Factors among Adult Inpatients at Public Hospitals of Harari Regional State, Eastern Ethiopia

Abstract: Introduction Globally, depression is one of the three leading causes of disease and it will be the second leading cause of world disability by 2030. The prevalence of depression in Sub-Saharan Africa ranges from 15 to 30%. In Ethiopia, depression was found to be the seventh leading cause of disease burden and its prevalence has been increased in hospital compared to community setting because hospital environment itself is stressful. Yet, no study was done in Eastern Ethiopia, where substance use like Khat is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
5
10
3
Order By: Relevance
“…Our study result also con rmed that those who didn't had social support had found to be more depressed compared to those who responded that they had social support. This study result is higher than study done in public hospitals of eastern Ethiopia [17]. The difference could be the study participants involved in Harar hospitals were those admitted patients in a ward.…”
Section: Discussioncontrasting
confidence: 65%
“…Our study result also con rmed that those who didn't had social support had found to be more depressed compared to those who responded that they had social support. This study result is higher than study done in public hospitals of eastern Ethiopia [17]. The difference could be the study participants involved in Harar hospitals were those admitted patients in a ward.…”
Section: Discussioncontrasting
confidence: 65%
“…The prevalence of this study was relatively lower than from the studies conducted in Pakistan, Harari Regional State, Debre Markos and Felege Hiwot hospitals and Gondar University hospitals, Ethiopia were 87.9%, 59.7%, 61% and 58.6% respectively (16)(17)(18)(19). This variation might be resulted from making mental health as global prioritizing problems, change in improving policy, service development and management protocol on mental health related problems (20,21) and life style modi cation of patients, change in patient safety with in and after discharge the hospitals, relatively increase mental and psychological counseling and even change in methodological approach might be also the possible difference.…”
Section: Discussioncontrasting
confidence: 62%
“…Regional State hospitals of Ethiopia respectively (13,17,22,24,30,32,34). This outcome might be resulted from inpatients with two or more chronic comorbid disorder might have different physical illness and the self-reporting questionnaire diagnostic tool also included some symptoms of physical illness and patients with comorbid disorder were limited from their daily physical activities; which might result to high report of mental distress (11).…”
Section: Discussionmentioning
confidence: 99%
“…This study result is higher than a study done in public hospitals of Eastern Ethiopia. 17 The difference could be that the study participants involved in "Harar" hospitals were those admitted patients in a ward.…”
Section: Discussionmentioning
confidence: 99%